Huntington's Disease Molecular Pathogenesis and Current Models - Ersoy Tunalı, Nagehan (IntechOpen, 2017)
Huntington's disease is a progressive neurodegenerative disorder of the brain. It is one of the quite devastating and currently incurable human conditions. Degeneration of specific types of neurons in the brain results in a triad of clinical features: serious behavioral disturbances, uncontrolled movements of body parts, and deterioration of intellectual capabilities. The underlying complex mechanisms and molecular players of the cellular cascades still need to be deciphered in detail despite considerable advances. Once solved, the related molecular mechanisms will not only enlighten the HD story but will also shed light on other polyglutamine diseases and similar brain disorders. This book, Huntington's Disease-Molecular Pathogenesis and Current Models, is planned to cover recent scientific achievements in understanding the cellular mechanisms of HD. The chapters provide comprehensive description of the key issues in HD research. In this regard, this book will serve as a source for clinicians and researchers in the field and also for life science readers in increasing their understanding and awareness of the clinical correlates, genetic aspects, neuropathological findings, and potential therapeutic interventions related to HD.